Institutional Goals of Sustainability in the Context of Higher Education-Contribution - Medani P. Bhandari (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej)
This brief conceptual paper on sustainability defines sustainability, its development paradigms related sustainable development 17 goals with special focus on Goal 16; which states “Promote peaceful and inclusive societies for sustainable development, provide access to justice for all and build effective, accountable and inclusive institutions at all levels”. The goal 16 also focuses on institutionalized mechanism to attain the desired outcome. Institutions have to follow the organized pattern grounded on the societal -political, economic, social norms and patterns. This paper simply shows the pattern of how United Nations has been focusing on institutionalization of sustainable development agendas particularly since UN Conference on Environment and Development (UNCED) in Rio de Janeiro in 1992, which also formalized the Commission on Sustainable Development (CSD). There is no doubt that; to formalization of sustainability concept, higher education institutions have been playing critical roles. Based on secondary information, this paper gives a general view of how higher educational institutions initiation to achieve SDGs.